2011
DOI: 10.1080/1536710x.2011.555251
|View full text |Cite
|
Sign up to set email alerts
|

Firm-Specific Managerial Experience and the Social Capital–Performance Relationship in a Sub-Saharan African Transition Economy

Abstract: The authors examine the direct and moderating effects of firm-specific managerial experience on the relationship between social capital and performance. Using data from Ghana, the findings show that social capital from bureaucratic officials and community leaders, as well as firmspecific managerial experience, have a positive influence on performance, while social capital from politicians has a negative influence on firm performance. Furthermore, firm-specific managerial experience positively moderates the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Furthermore, logistics regression tests conducted also found a significant statistical relationship between the use of customers and small firm growth in employment. This result is consistent with earlier finding by Acquaah and Appiah-Nkrumah (2011) that the use of specific social capital sources has significant influence on firm performance, thereby contributing to firm’s social capital literature.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, logistics regression tests conducted also found a significant statistical relationship between the use of customers and small firm growth in employment. This result is consistent with earlier finding by Acquaah and Appiah-Nkrumah (2011) that the use of specific social capital sources has significant influence on firm performance, thereby contributing to firm’s social capital literature.…”
Section: Discussionsupporting
confidence: 93%
“…Contrary to conventional wisdom (cf. Nahapiet and Ghoshal ), three of these studies (Acquaah and Appiah‐Nkrumah ; Godesiabois ; Malik ) have observed statistically significant linear negative relationships, while three other studies (Laursen et al . ; Villena et al .…”
Section: Reviewing the Negative Effectsmentioning
confidence: 93%
“…Relationship of Social Capital with Innovation Strategies. Social capital is the basis for the formation of synergy in carrying out organizational tasks that will determine innovation (Huang et al, 2010;Acquaah and Appiah-Nkrumah, 2011;Lightfoot and Gebauer, 2011). The broader the relationship of a person and the wider social networking (social networking) the higher a person's value (Brown, 2010;Ahmad et al, 2011;Cerne et al, 2013).…”
Section: Resultsmentioning
confidence: 99%